Coronal plane changes in fixed‐ versus mobile‐bearing unicompartmental knee replacements: Clinical and revision outcomes - Enejd Veizi; Şahan Güven; Başak Sinem Sezgin; Christos Koutserimpas; Nevzat Arıcan; Ahmet Fırat; Çetin Işık; Murat Bozkurt (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose To investigate the relationship between coronal plane changes after mobile‐ and fixed‐bearing (MB and FB) unicompartmental knee replacement (UKR) and clinical outcomes while also comparing revision rates and joint awareness between the two surgical modalities. Methods Patients who operated between 2014 and 2017 with a UKR (FB or MB) were eligible for inclusion. Inclusion criteria were a minimum follow‐up of 5 years, presence of clinical outcome scores, Forgotten Joint Scores and radiological data (joint obliquity angles, tibial component alignment, angle between the medial and lateral joint lines, change in overall knee alignment, change in the medial proximal tibial angle). Outcome variables were compared between the MB and FB UKRs, and correlation analyses were performed to assess the effect of radiological changes on clinical and awareness scores. Two separate researchers performed all radiological measurements on direct radiographs. Results Out of 229 patients, 197 were eligible for inclusion. Basic demographic data (mean age, sex, body mass index and follow‐up time) were comparable between the FB and MB groups. There were more revisions in the mobile bearing group (6.5% vs. 12.5%), though the results did not reach statistical significance. Clinical outcomes and joint awareness were similar in the two groups. Overall, the change in joint line obliquity or alignment was comparable between the groups. Conclusions Clinical outcomes and joint awareness scores are similar in both fixed and mobile‐bearing UKRs. Revision is more frequent, though not statistically significant, following an MB UKR. Overall, change in knee alignment and medio‐lateral joint lines is similarly well tolerated in both implant modalities. Level of Evidence Level III.